Really Fake: The Magic Circle, the Mundane Circle, and the Everyday - Zimmerman, Joshua (Eludamos: Journal for Computer Game Culture, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> This article focuses on how the “everyday" has colonized and complicated the virtual world. Using examples drawn primarily from Sony Online Entertainment's Everquest 2, I explore the way that both the institutional force of the everyday and mundane objects such as tables and chairs have come to be a major part of play in MMORPGs. In exploring these topics, I consider the possibility of a "mundane circle" in which mundane objects and activities exist in a fantasy setting. I also examine how the presence of these mundane objects refreshes the fantasy world. In the end, I question whether play can truly be called so when the virtual world is so reminiscent of the real world.